On-demand and location selective particle assembly via electrophoretic deposition for fabricating structures with particle-to-particle precision - Qian, Fang (Langmuir : the ACS journal of surfaces and colloids, 2015)
Programmable positioning of 2 μm polystyrene (PS) beads with single particle precision and location selective, "on-demand", particle deposition was demonstrated by utilizing patterned electrodes and electrophoretic deposition (EPD). An electrode with differently sized hole patterns, from 0.5 to 5 μm, was used to illustrate the discriminatory particle deposition events based on the voltage and particle-to-hole size ratio. With decreasing patterned hole size, a larger electric field was required for a particle deposition event to occur in that hole. For the 5 μm hole, particle deposition began to occur at 10 V/cm where as an electric field of 15 V/cm was required for particles to begin depositing in the 2 μm holes. The likelihood of particle depositions continued to increase for smaller sized holes as the electric field increased. Eventually, a monolayer of particles began to form at approximately 20 V/cm. In essence, a voltage threshold was found for each hole pattern of different sizes, allowing fine adjustments in pattern hole size and voltage to control when a particle deposition event took place, even with the patterns on the same electrode. This phenomenon opens a route toward controlled, multimaterial deposition and assembly onto substrates without repatterning of the electrode or complicated surface modification of the particles. An analytical approach using the theories for electrophoresis and dielectrophoresis found the former to be the dominating force for depositing a particle into a patterned hole. Ebeam lithography was used to pattern spherical holes in precise configurations onto electrode surfaces, where each hole accompanied a polystyrene (PS) particle placement and attachment during EPD. The versatility of e-beam lithography was utilized to create arbitrary pattern configurations to fabricate particle assemblies of limitless configurations, enabling fabrication of unique materials assemblies and interfaces